Diagnostic tools for assessment of urinary dysfunction in MS patients without urinary disturbances - Ghezzi, A.; Mutta, E.; Bianchi, F.; Bonavita, S.; Buttari, F.; Caramma, A.; Cavarretta, R.; Centonze, D.; Coghe, G. C.; Coniglio, G.; Del Carro, U.; Ferrò, M. T.; et al. (Neurological sciences, 2016)
Many guidelines are available for the management of lower urinary tract symptoms (LUTSs) in multiple sclerosis (MS) patients, but no agreement exists on the best approach for subjects without LUTSs. The objective of this study was to evaluate whether LUTSs can be detected in MS patients asymptomatic for urinary dysfunction, comparing three different tools [measure of post-void residual volume (PRV), bladder diary (BD), a focused questionnaire (IPSS)], and whether disability, disease duration and signs of pyramidal involvement are linked to their subclinical presence. 178 MS patients (118 women) have been included (mean age 41.2 years, mean disease duration 11.3 years, mean EDSS 2.2), and tested with the above-mentioned tools. PRV was abnormal in 14 subjects (7.8 %), associated to abnormal findings at IPSS in 3 cases, at BD in 2 cases, at both in 1. BD was abnormal in 37 subjects (20.8 %), with concomitant abnormal PRV in 2, abnormal IPSS in 10 cases, abnormal IPSS and BD in 1. IPSS was ≥ 9 in 43 subjects (24.1 %). At least one test was abnormal in 76 patients (42.7 %): 1 in 57 patients (32.0 %), 2 in 17 (9.5 %), and 3 tests in 2 (1.1 %). Patients with at least one abnormal urinary variable, compared to patients without urinary abnormalities, had a more frequent pyramidal involvement (69.5 vs. 16.8 %, χ 2 = 48.6, p < 0.00001), a more frequent occurrence of EDSS ≥2 (83.1 vs. 23.5 %, χ 2 = 56.9, p < 0.00001), and a longer disease duration (15.7 ± 7.3 vs. 9.1 ± 7.1, t = 5.7, p < 0.00001). Asymptomatic LUTS were frequent but none of the tests used permitted to better identify asymptomatic patients.